Evaluation in zebrafish model of the toxicity of rhodamine B‐conjugated crotamine, a peptide potentially useful for diagnostics and therapeutics. Issue 11 (16th August 2017) - Chan, Judy Yuet‐Wa; Zhou, Hefeng; Kwan, Yiu Wa; Chan, Shun Wan; Radis‐Baptista, Gandhi; Lee, Simon Ming‐Yuen
Abstract: Crotamine is defensin‐like cationic peptide from rattlesnake venom that possesses anticancer, antimicrobial, and antifungal properties. Despite these promising biological activities, toxicity is a major concern associated with the development of venom‐derived peptides as therapeutic agents. In the present study, we used zebrafish as a system model to evaluate the toxicity of rhodamine B‐conjugated (RhoB) crotamine derivative. The lethal toxic concentration of RhoB‐crotamine was as low as 4 μM, which effectively kill zebrafish larvae in less than 10 min. With non‐lethal concentrations (<1 μM), crotamine caused malformation in zebrafish embryos, delayed or completely halted hatching, adversely affected embryonic developmental programming, decreased the cardiac functions, and attenuated the swimming distance of zebrafish. The RhoB‐crotamine translocated across vitelline membrane and accumulated in zebrafish yolk sac. These results demonstrate the sensitive responsivity of zebrafish to trial crotamine analogues for the development of novel therapeutic peptides with improved safety, bioavailability, and efficacy profiles.